In vitro evaluation of the antimicrobial activity of a castor oil-based irrigant - Leonardo, Mario Roberto [UNESP] (Wolters Kluwer, 2001)
The antimicrobial activity of irrigating solutions - Endoquil (castor oil detergent), 2% chlorhexidine gluconate solution, and 0.5% NaOCI solution - was evaluated against Gram-positive cocci (Micrococcus luteus, Staphylococcus aureus, Enterococcus faecalis, Staphylococcus epidermidis, Streptococcus mutans, and Streptococcus sobrinus), Gramnegative rods (Escherichia coli and Pseudomonas aeruginosa), and the yeast Candida albicans. Activity was evaluated using the two-layer agar diffusion technique. The base layer was obtained by pouring 10.0 ml of Muller Hinton Medium or 10.0 ml of Brain Heart Infusion agar in a Petri dish. After solidification a 5.0 ml seed layer of Muller Hinton Medium or Brain Heart Infusion agar with inoculum (106/ml) was added. Absorbent paper disks (6.0 mm in diameter) immersed in the solutions were placed at equidistant points. Plates were maintained at room temperature for 2 h for prediffusion of the solutions and incubated at 37°C for 24 h. The candle jar system was used for the Brain Heart Infusion agar plates. All tests were performed in duplicate. After incubation the medium was optimized with 0.05 g% triphenyltetrazolium chlorate gel and inhibition halos were measured. All bacterial strains were inhibited by 2.0% chlorhexidine gluconate. Endoquil was effective against Grampositive microorganisms, and 0.5% NaOCI was effective only against S. aureus. Copyright © 2001 by The American Association of Endodontists.
Keywords: Anti Infective Agents, Local; biomedical and dental materials; castor oil; chlorhexidine; chlorhexidine gluconate; drug derivative; hypochlorite sodium; topical antiinfective agent; Candida albicans; comparative study; drug effect; Gram negative bacterium; Gram positive cocci; microbiological examination; Anti-Infective Agents, Local; Castor Oil; Chlorhexidine; Comparative Study; Gram-Negative Bacteria; Gram-Positive Cocci; Microbial Sensitivity Tests; Root Canal Irrigants; Sodium Hypochlorite